Triclosan activates c-Jun/miR-218-1-3p/SLC35C1 signaling to regulate cell viability, migration, invasion and inflammatory response of trophoblast cells in vitro - Huo, Weiwei; Wang, Ying; Chen, Ting; Cao, Tianyue; Zhang, Yue; Shi, Zhouhong; Hou, Shunyu (BMC pregnancy and childbirth, 2022)
Spontaneous abortion is considered as the commonest complication of pregnancy. Triclosan (TCS) is an antimicrobial agent, which participates in the process of multiple human diseases, including spontaneous abortion. Our study aimed to evaluate the effect of TCS on spontaneous abortion and disclose the possible regulatory mechanism in vitro. RT-qPCR analyzed that miR-218-1-3p derived from abortion-associated factor slit guidance ligand 2 (SLIT2) was up-regulated in trophoblast cells under TCS treatment. Supported by western blot analysis, functional experiments demonstrated that miR-218-1-3p overexpression impeded the proliferation, migration and invasion while exacerbating the inflammatory response of trophoblast cells. Moreover, mechanism assays revealed that TCS modulated c-Jun production to promote MIR218-1 transcription and enhance miR-218-1-3p expression. Moreover, solute carrier family 35 member C1 (SLC35C1) was validated as a target gene of miR-218-1-3p, and miR-218-1-3p was sustained to negatively modulate SLC35C1 expression in trophoblast cells. Rescue assays validated the role of TCS/miR-218-1-3p/SLC35C1 axis in regulating the viability, migration, invasion and inflammatory response of trophoblast cells. TCS regulated miR-218-1-3p/SLC35C1 axis to modulate the proliferation, migration, invasion and inflammatory response of trophoblast cells in vitro, which might provide novel insights for spontaneous abortion prevention.